Varactor‐tunable dual‐band filtering low‐noise amplifier. Issue 5 (8th April 2018) - Kumar, Amarjit; Pathak, Nagendra P.
Abstract: Design and development of a tunable dual‐band filtering LNA has been presented in this paper. The center frequency of the lower band is continuously tuning with applied dc voltages. The center frequency of lower band has a tuning range of 2.0–2.5 GHz; while that of upper band is fixed at 5 GHz. Power consumption of our circuit is 28 mW. Overall size of proposed device is 0.96λg × 0.34λg, where λg is the guided wavelength at lower frequency. One ATF36163 GaAs HEMT is used as the active device in our circuit. Measured per stage gain of lower band is varying from 8 to 1.6 dB; while that of upper band is 5.4 dB. Measured noise figure of lower band is 2.4–3.4 dB; while that of upper band is 2.5 dB. Proposed filtering LNA has improved selectivity and spurious harmonic suppression with measured stopband attenuation of 45 dB. To author's knowledge, the investigation of tunable multiband and multifunctional device for highly improving the level of integration of the multiband RF front‐end design is reported for the first time.